Two new species of the genus Cymatopus Kertész from the Mariana Islands (Diptera: Dolichopodidae) - Masunaga, Kazuhiro; Evenhuis, Neal L. (Zootaxa, 2012)
Two new species of the genus Cymatopus Kertész, 1901, C. femoralis sp. nov. and C. ventralis sp. nov., are described andillustrated from Pagan, Saipan, Rota, and Guam. This is the first record of Cymatopus from the Mariana Islands. A key to all known species of the genus is provided.